2021
DOI: 10.1503/jpn.200128
|View full text |Cite
|
Sign up to set email alerts
|

Error-related negativity predicts increases in anxiety in a sample of clinically anxious female children and adolescents over 2 years

Abstract: Background: An increased neural response to making errors has emerged as a biomarker of anxiety. Error negativity (Ne) or errorrelated negativity (ERN) is an event-related potential generated when people commit errors; the Ne/ERN is greater among people with anxiety and predicts increases in anxiety. However, no previous study has examined whether the Ne/ERN can be used as a prognostic indicator among people with current anxiety. The present study addressed this gap by examining whether the Ne/ERN prospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…We, and others, have examined the potential utility of the ERN as a risk marker in large, longitudinal samples. Results are consistent across all studies: a potentiated ERN relates to increased anxiety prospectively (Filippi et al, 2020;Lahat et al, 2014;McDermott et al, 2009;Meyer, Danielson, et al, 2017;Meyer et al, 2015Meyer et al, , 2021Meyer, Nelson, et al, 2018). One of our studies found that an increased ∆ERN predicted the onset of new anxiety disorders in children between the ages of 6 and 9 years old, even while controlling for baseline anxiety symptoms and maternal history of anxiety (Figure 5; Meyer et al, 2015).…”
Section: The Ern As a Risk Marker Of Anxietysupporting
confidence: 81%
See 1 more Smart Citation
“…We, and others, have examined the potential utility of the ERN as a risk marker in large, longitudinal samples. Results are consistent across all studies: a potentiated ERN relates to increased anxiety prospectively (Filippi et al, 2020;Lahat et al, 2014;McDermott et al, 2009;Meyer, Danielson, et al, 2017;Meyer et al, 2015Meyer et al, , 2021Meyer, Nelson, et al, 2018). One of our studies found that an increased ∆ERN predicted the onset of new anxiety disorders in children between the ages of 6 and 9 years old, even while controlling for baseline anxiety symptoms and maternal history of anxiety (Figure 5; Meyer et al, 2015).…”
Section: The Ern As a Risk Marker Of Anxietysupporting
confidence: 81%
“…Considering the fact that the ERN is increased in anxious individuals (Meyer, 2016(Meyer, , 2017, predicts risk for future increases in anxiety among healthy and anxious populations (Meyer et al, 2021), and may be elevated early in the course of development, (i.e., before anxiety has become impairing, (Meyer et al, 2015), it is important to better understand what factors contribute to the development of the ERN early in life. While some of the variance in the ERN is heritable, a large portion of the variance appears to be impacted environmental factors (40-60%; Anokhin et al, 2008).…”
Section: Factors That Shape the Ernmentioning
confidence: 99%
“…Results suggested that for younger children, more frequent interpersonal dependent stressors predicted a larger ERN, but this effect was not significant in older children or adolescents. Additionally, as prior studies using this dataset have examined the associations between the ERN and anxiety ( Meyer et al, 2018 , Meyer et al, 2021 ) and puberty ( Gorday and Meyer, 2018 ), we assessed whether anxiety or pubertal stage moderated the association between interpersonal dependent stressors and the ERN. While anxiety was not found to significantly moderate the relationship between the ERN and stressors, child pubertal stage was a significant moderator, such that for less pubertally developed children, more frequent interpersonal stressors predicted a larger ERN, even when controlling for child age.…”
Section: Discussionmentioning
confidence: 99%
“…The present sample was drawn from a larger, NIMH-funded, longitudinal study (R01 MH097767) investigating neural risk markers for depression in females from a community sample. It is important to note that previous studies have been published using this dataset ( Chong et al, 2020 , Gorday and Meyer, 2018 , Meyer et al, 2018 , Meyer et al, 2021 ); however, none of the previous studies focused on the relationship between the ERN and stressful life events. Previous studies using this larger dataset have investigated the relationship between anxiety and the ERN ( Meyer et al, 2018 , Meyer et al, 2021 ), parenting styles and the ERN ( Chong et al, 2020 ), and puberty and the ERN ( Gorday and Meyer, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation